A Conceptual Framework for Timber Adoption in the Construction Industry - Verhage, B.; Hassan, F.S.; Grobbelaar, S. (South African Journal of Industrial Engineering, 2025)
This study explored the key human behavioural factors influencing the adoption of timber and engineered wood products in the construction industry by integrating the key constructs of the theory of planned behaviour and the unified theory of acceptance and use of technology. The study identified relationships between attitude towards behaviour and performance expectancy, subjective norm and social influence, perceived behavioural control and facilitating conditions, and effort expectancy in the context of timber adoption. The proposed framework provides a theoretical foundation for further research on the adoption of timber in the construction industry.